Navigating the maze of polycystic ovarian syndrome enquiries with ChatGPT - Nayak, Anurupa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
ChatGPT is a form of generative AI, a tool created by OpenAI and launched in November 2022. It lets users enter prompts to receive human-like texts or images, that are created by AI. ChatGPT is trained with reinforcement learning through human feedback and reward models that rank the best responses. ChatGPT works through its Generative Pre-trained Transformer, which uses specialized algorithms to find patterns within data sequences. Users can ask ChatGPT a variety of questions, including simple or more complex ones, such as, “What is the meaning of life?” or “What is the history behind the invention of the telephone?”. However, ChatGPT uses data up to the year 2021, so it has no knowledge of events and data past that year.